BUSSINESS ANALYSIS OF SQUID (Loligo sp) FISHING EFFORT WITH FISHING GEAR BOUKE AMI (Stick Held Dip Net) LANDED AT HARBOR FISHERY OCEAN OFNORTH SUMATERA PROVINCE - Simarmata, Alfrendo; Hendrik, Hendrik; Hamid, Hamdi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT  This research was conducted on March 5-22, 2018 at Belawan Ocean Fishing Port. The purpose of this study is to find out how much investment capital and net income, analyzing how feasibility of business if reviewed based on investment criteria from the business of squid fishing vessels 30 GT and 40 GT ships. This study also aims to see how the sensitivity of the catching of squid by means of catching bouke ami is seen from the investment criteria.  The results showed that the total investment for equipment business bouke ami ship 30 GT for IDR.1.345.470.000 and 40 GT ships amounting to IDR.1.499.880.000. As for the net income per year of 30 GT boats amounting to IDR.495.850.000 and 40 GT boats amounting to IDR.627.700.000. The investment criteria for bouke ami 30 GT vessel business is obtained NPV value IDR.1.262.015.050, BCR 1.20, IRR 67,11% (IRR> i) and For boiler business ami 40 GT got value NPV IDR.1.813.371.100, BCR 1.28, IRR 87.93% (IRR> i).Based on the calculation of sensitivity analysis within 10 years from both types of vessel size, it can be concluded that the fishing gear business of bouke ami will experience losses if there is a 10% cost increase and 10% decrease in production in the fourth scenario. Where for the NPV value of the two vessel sizes are negative, the BCR is <1, and the IRR is smaller than the highest interest rate per year, then the business is better stopped if the fishing gear business bounce experiencing the incident like this. Keywords : Capture Equipment Bouke Ami, Investment, Income, Financial Analysis,    Sensitivity Analysis.